2018
DOI: 10.2147/jpr.s182322
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous process decompression is associated with a reduction in opioid analgesia in patients with lumbar spinal stenosis

Abstract: BackgroundLumbar spinal stenosis (LSS) causes significant pain and functional impairment, and medical management has increasingly included the prescription of opioid-based analgesics. Interspinous process decompression (IPD) provides a minimally-invasive treatment option for LSS.MethodsThis study estimated the type, dosage, and duration of opioid medications through 5 years of follow-up after IPD with the Superion Indirect Decompression System (Vertiflex Inc., Carlsbad, CA USA). Data were obtained from the Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Research has shown that interspinous process spacer devices can provide relief for patients with lumbar spinal stenosis with neuroclaudication. 237,238 Regenerative/adult autologous stem cell therapy may show promise in the treatment of multiple painful conditions. -241 Further research is needed and encouraged to investigate the potential of these therapies.…”
Section: Gaps and Recommendationsmentioning
confidence: 99%
“…Research has shown that interspinous process spacer devices can provide relief for patients with lumbar spinal stenosis with neuroclaudication. 237,238 Regenerative/adult autologous stem cell therapy may show promise in the treatment of multiple painful conditions. -241 Further research is needed and encouraged to investigate the potential of these therapies.…”
Section: Gaps and Recommendationsmentioning
confidence: 99%
“…Several IPD brands are available, including X-STOP (Medtronic, Minneapolis, MN), Coflex (Paradigm Spine, New York, NY), Helifix (Alphatec, Carlsbad, CA), Stenofix (Depuy Synthes, Raynham, MA), FLEXUS (Globus, Audubon, PA), Device for Intervertebral Assisted Motion (DIAM) (Medtronic, Minneapolis, MN), Aperius (Medtronic, Minneapolis, MN), Wallis (Zimmer Biomet, Warsaw, IN), and the Superion (Vertiflex/Boston Scientific, Marlborough, MA) (2)(3)(4). Efficacy studies have shown an improvement in back and leg pain, functional outcome scores, and reduced the opioid medication requirement compared to conservative therapy (5)(6)(7)(8)(9)(10)(11). However, the optimal role of IPDs relative to surgical decompression remains unclear (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, it has not been applied for periprocedural analgesia of minimally invasive interspinous space decompression. Interspinous decompression is increasingly a treatment option for symptomatic lumbar spinal stenosis, with clinical evidence suggesting reduction in opioid analgesia requirements [ 2 ] and sustained five-year outcome improvements in function and quality of life [ 3 ]. In particular, interspinous spacers are finding a role as a percutaneous alternative to surgical options for elderly patients who may have significant medical co-morbidities that may preclude more open or extensive surgical procedures [ 4 ].…”
Section: Introductionmentioning
confidence: 99%